2020
DOI: 10.2147/cmar.s270200
|View full text |Cite
|
Sign up to set email alerts
|

<p>Adipose Mesenchymal Stem Cell-Derived Exosomal microRNA-1236 Reduces Resistance of Breast Cancer Cells to Cisplatin by Suppressing SLC9A1 and the Wnt/β-Catenin Signaling</p>

Abstract: Background: Emerging evidence has noted the versatile functions of mesenchymal stem cell-derived exosomes (MSC-Exos) in cancer control. This work aims to probe to function of adipose MSC-Exos (adMSC-Exos) in drug-resistance of breast cancer (BC) cells to cisplatin (DDP) and the molecules involved. Methods: Parental and DDP-resistant BC cell lines MCF-7 and MDA-MB-231 were used. All cells were pre-treated with adMSC-Exos. Then, the viability and apoptosis of cells after DDP treatment were determined. Differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…EMT is a process that converts polarized in treatment sensitive cells through the transfer of miR-155 [ 304 ]. Adipose mesenchymal stem cell-derived miR-1236 in exosomes sensitized the breast cancer cells to cisplatin treatment by inhibiting the Wnt/β-catenin signaling [ 305 ]. Exosomes obtained from human umbilical cord mesenchymal stem cells exhibit inhibitory effects on the breast cancer cells in vitro and in vivo.…”
Section: Recent Advancement In Breast Cancer Treatmentmentioning
confidence: 99%
“…EMT is a process that converts polarized in treatment sensitive cells through the transfer of miR-155 [ 304 ]. Adipose mesenchymal stem cell-derived miR-1236 in exosomes sensitized the breast cancer cells to cisplatin treatment by inhibiting the Wnt/β-catenin signaling [ 305 ]. Exosomes obtained from human umbilical cord mesenchymal stem cells exhibit inhibitory effects on the breast cancer cells in vitro and in vivo.…”
Section: Recent Advancement In Breast Cancer Treatmentmentioning
confidence: 99%
“…The study suggests that MSCs can increase β-catenin expression and stimulate Wnt activity by MSC-secreted soluble factors and the previously mentioned molecular mechanisms [ 82 ]. On the other hand, there is research that underscores the importance of MSCs in inhibiting the proliferation, invasion, and migration of cancer cells through the Wnt signaling pathway [ 83 , 84 ]. It has been reported that MSC-derived exosomes containing miR-133b suppress glioma development by inhibiting EZH2 and the Wnt/β-catenin signaling pathway [ 83 ].…”
Section: Therapeutic Strategies Based On Mscsmentioning
confidence: 99%
“…Recent studies have also shown that exosomes derived from MSCs may play a significant role in cancer control. Jia et al found that adipose derived MSC-exosomes containing miR-1236 increase the sensitivity of breast cancer to cisplatin with the involvement of SLC9A1 downregulation and Wnt/β-catenin inactivation [ 84 ]. Torsvik et al indicate that tumor growth can also be inhibited by MSC secreted inflammation cytokines, by Dkk-1 and the subsequent inhibition of the Wnt/β-catenin pathway [ 78 ].…”
Section: Therapeutic Strategies Based On Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes derived from adipose tissue mesenchymal stem cells contain miR-1236, which down-regulates Solute Carrier Family 9 Member A1 (SLC9A1) and the Wnt/b-catenin pathway. 94 This sensitizes the breast cancer cells to cisplatin treatment. Another study 95 showed increased resistance to doxorubicin in breast cancer cells in the presence of adipocytes.…”
Section: Adipocytesmentioning
confidence: 99%